Dinamika Pengembangan Sistem Pendidikan (Kerangka Dasar Potensi Anak Usia Dini) - Nasir, Amin (PIAUD Universitas Islam Negeri Sunan Kudus, 2014)
The pattern of learning in early childhood should be built basedon the growth and development of children whose implementation is packedappropriately in accordance with the child’s world, that is playing, drawing,singing and watching cartoons. All of them are a routine activity that is greatfun for children, as well as through playing, drawing, singing children will learnGrowth of children is different with their development. The growth is morequantitative, whereas the development refers to the qualitative parameters.Thus, the meaning of early childhood development is the advancement of thequality of physical function, psychological and synergy of both. Early childhooddevelopment that need to be considered further attention include areas: motorskills, physical function, cognitive ability, language skills, and the ability ofreligion.